Geriatric social security and welfare services in Gwalior, India: a cross sectional study of awareness, utilization, concerns and solutions - Dwivedi, Shatkratu; Tiwari, Ranjana; Sahu, Rupesh; Bansal, Manoj; Sharma, Vikash; Singh, Sumit Bhadoria; Kuity, Paromita; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2020)
Background: Between 2015 and 2050, the proportion of the world's population over 60 years will nearly double from 12% to 22%. In 2050, 80% of older people will be living in low and middle income countries. All countries face major challenges to ensure that their health and social systems are ready to make the most of this demographic shift. Methods: The present Study was a cross-sectional study done for 1 year in 2016 in which 600 households were selected by simple random sampling in Gwalior city in which the knowledge and awareness of various Government health scheme and policies and their day to day utilization in their life were assessed. A predesigned and pretested interview based structured questionnaire was used for data collection. They were analysed and interpreted by appropriate software and various statistical tests were applied. Results: The maximum no. of participants 112 (54.9%) knew about railways/road transport/air travel concessions provided to Senior citizens, 23.04% knew about telephone and postal services, 13.24% were aware of tax exemptions while 9.8% knew about banking and insurance schemes regarding elderly. Males were generally more aware than females. The maximum utilization (59.82%) was found in railways/road transport/air travel concessions while minimum utilization (25.00%) was in Indira Gandhi National old age pension scheme. Conclusions: The system for comprehensive geriatric care to the community was well in place with regular development and growth but there is dearth of awareness and utilization of these services.